The Thai translation of un violador en tu camino : a multimodal critical discourse analysis - Jooyin Saejang (Penerbit Universiti Kebangsaan Malaysia, 2023)
In Thailand, the advocacy group Feminist Liberation that emerged alongside the pro-democracy protests in mid-2020 following the COVID-19 pandemic translated Un violador en tu camino, a song composed and performed publicly by Chilean feminist collective Las Tesis and since hailed as a feminist anthem, into Thai as Sita Lui Fai and adapted the original choreography to construct their public discourse around gender-based violence. To answer the overarching question of how transnational feminism was enabled by translation, this paper investigates how the Chilean feminist discourse has changed upon introduction into the target context using Kress and van Leeuwen’s (2006) multimodal critical discourse analysis of the Thai translation and its choreography. The results show that while both versions similarly highlight the structural cause of gender-based violence, the Chilean lyrics place greater focus on feminist theoretical pedagogy in contrast to the Thai translation’s function as an affective vehicle for anger as exemplified by the adoption of a more colloquial term for “patriarchy”, the choice of specific pronouns to challenge Thai seniority culture, and the emotionally charged modifications to the original choreography. With multiple references to the monarchy, the song has been re-signified to reflect the reality of gender oppression specific to Thailand. Translation has thus served as a tool through which transnational feminism has been fostered. Feminist Liberation’s collaboration with other advocacy groups additionally indicated their intersectional framework where LGBTQ+ rights, reproductive healthcare, students’ rights are inextricably linked to the goal of gender equality.